EFFECT OF DIETARY LIPIDS AND ALFALFA LEAF MEAL ON SERUM LIPIDS PROFILE OF RATS - A. Abdel Atti, Khadiga; K. Elnowrani, Mohammed; M.Dousa, d Bakheit (Journal of Veterinary Medicine and Animal Production, 2022)
Twenty seven 2 to 3 month old Wister albino male rats were used to determine the serum lipids of rats fed ration containing boiled egg yolk (BEY), cooked beef burger (CBB) and alfalfa leaf meal (ALM). The treatments were T1 basal diet as control (mixture of wheat bran, corn, maize oil, premix, calcium bicarbonate and salt), T2 basal diet supplemented with 15g BEY + 45g CBB daily and T3 basal diet supplemented with 15g BEY + 45g CBB + 5g alfalfa leaf meal daily. The experiment was arranged in a completely randomized design (CRD) with 3 treatments each replicated three times with 3 rats per replicate, and the experiment lasted for six weeks. Blood samples were collected for determined serum cholesterol, triglyceride, low density lipoprotein (LDL) and high density lipoprotein (HDL). The result showed that feeding lipids source (T2 = egg yolk and beef burger) caused a significant increased (P < 0.01) serum cholesterol, triglyceride, low density lipoprotein and high density lipoprotein of rats than control diet (T1). Feeding alfalfa leaf meal (T3) significantly (P < 0.01) decreased serum cholesterol, triglyceride and low density lipoprotein. Moreover, alfalfa leaf meal (T3) significantly (P < 0.01) increased serum high density lipoprotein of rats.